The Influence of Motivation, Personality, and Social Environment on Students' Religious Awareness in the Madrasah Aliyah Dormitory - Muhamad Solihin; Saipul Annur; Yuniar Yuniar; Indah Wigati; Muhammad Torik (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study aims to analyze the influence of motivation, personality, and social environment on the religious awareness of students residing in the dormitory of Madrasah Aliyah Negeri 1 Lahat Regency. This study employed a quantitative approach using a correlational research design with a cross-sectional survey. The population consisted of 220 dormitory students, and 110 respondents were selected through simple random sampling. Data were collected using structured Likert-scale questionnaires and supported by documentation. The data were analyzed using descriptive statistics, partial hypothesis testing (t-test), and simultaneous hypothesis testing (F-test) at a 5% significance level. The findings reveal that motivation has a positive and significant effect on students’ religious awareness (t = 3.25; p = 0.002), indicating that stronger learning and spiritual motivation contributes to higher religious awareness. Personality also has a significant effect (t = 2.80; p = 0.007), suggesting that disciplined and responsible students demonstrate better religious awareness. Likewise, the social environment significantly influences religious awareness (t = 2.10; p = 0.040), highlighting the importance of a supportive dormitory climate, peer interaction, and teacher supervision. Simultaneously, motivation, personality, and social environment significantly affect religious awareness (F = 15.30; p = 0.000), explaining 62% of the variance, while the remaining 38% is attributed to factors beyond the scope of this study. These findings provide practical implications for dormitory supervisors, Islamic education teachers, and school leaders in strengthening students’ religious awareness through integrated motivational, character-building, and supportive environmental programs.